Finland’s Experience In Developing NaturalScientific Literacy Skills (Pedagogical Cluster-Journal of Pedagogical Developments, 2026)
This annotation briefly analyzes Finland’s experience in developing students’ natural-scientific literacy skills within the education system. In Finnish schools, the teaching process is based on competency-based approaches, interdisciplinary integration, and activity-oriented instruction. Special attention is given to fostering students’ independent thinking, critical analysis skills, and environmental awareness